2012
DOI: 10.1227/neu.0b013e3182535a00
|View full text |Cite
|
Sign up to set email alerts
|

What Patients With Gilles de la Tourette Syndrome Should Be Treated With Deep Brain Stimulation and What Is the Best Target?

Abstract: AbstractBACKGROUND:Gilles de la Tourette syndrome (GTS) is a chronic neurodevelopmental disorder characterized by tics and associated behavioral symptoms. Over the past decade, deep brain stimulation (DBS) has been increasingly advocated as a reversible and controllable procedure for selected cases of GTS.OBJECTIVE:We set out to answer 2 clinically relevant questions: what patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 124 publications
(305 reference statements)
0
8
0
Order By: Relevance
“…These regions included the right/left PMd (dorsal premotor cortex), the SMA (supplementary motor area), M1 (primary motor cortex), putamen (see, e.g. Grefkes et al ., ), and the thalami, which is a frequent target for deep brain stimulation (DBS) in GTS (Pansaon Piedad et al ., ). Finally, we selected the right superior frontal gyrus (rSFG area 6) because this region was hyperactivated in GTS patients (see Zapparoli et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…These regions included the right/left PMd (dorsal premotor cortex), the SMA (supplementary motor area), M1 (primary motor cortex), putamen (see, e.g. Grefkes et al ., ), and the thalami, which is a frequent target for deep brain stimulation (DBS) in GTS (Pansaon Piedad et al ., ). Finally, we selected the right superior frontal gyrus (rSFG area 6) because this region was hyperactivated in GTS patients (see Zapparoli et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…It was first used in 1997 179 and it has been estimated that around 100 DBS operations have been conducted to date. 180 DBS has predominantly been performed in adults -the youngest patients treated for TS being 16 years of age. 181 DBS has been applied to different areas of the basal ganglia and nearby structures, but the optimum target has been a source of controversy.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…181 DBS has been applied to different areas of the basal ganglia and nearby structures, but the optimum target has been a source of controversy. It appears that, although many different targets may be used, 180 different patients may benefit from stimulation of different areas of the brain. 181 There is little reported on adverse effects 177 but surgery-associated morbidity (e.g.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…In 2006, the first TSA guidelines proposed a minimum age criterion of 25 years to ensure that individuals who might experience spontaneous tic remission would not be implanted with a surgical device. Since that time, compelling arguments have been made for consideration of surgical intervention at younger ages in certain cases of severe TS . The risk–benefit data for TS and for other DBS indications have shown that the actual DBS procedure is safe and well tolerated in children, particularly as demonstrated in those with dystonia .…”
Section: Special Considerations Relevant To Ts Dbs and Guideline Updatesmentioning
confidence: 99%